2021
DOI: 10.1093/jmammal/gyab154
|View full text |Cite
|
Sign up to set email alerts
|

Human-provisioned foods reduce gut microbiome diversity in American black bears (Ursus americanus)

Abstract: The distal gut is home to the dynamic and influential gut microbiome, which is intimately linked to mammalian health by promoting and facilitating countless physiological functions. In a time of increased anthropogenic pressures on wildlife due to widespread habitat destruction, loss of natural prey/foods, and rapid urbanization, the study of wildlife gut microbiomes could prove to be a valuable tool in wildlife management and conservation. Diet is one of the most influential determinants of a host’s gut micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Our data provide the first insight into the microbial ecology of brown bears that are minimally impacted by human pressure. Previous research has shown that bears with access to processed foods (e.g., bait) have reduced GMB diversity that may negatively affect their health [21]. As such, our GMB data provide a benchmark against which the GMBs of brown bears…”
Section: Conservation Implicationsmentioning
confidence: 72%
See 1 more Smart Citation
“…Our data provide the first insight into the microbial ecology of brown bears that are minimally impacted by human pressure. Previous research has shown that bears with access to processed foods (e.g., bait) have reduced GMB diversity that may negatively affect their health [21]. As such, our GMB data provide a benchmark against which the GMBs of brown bears…”
Section: Conservation Implicationsmentioning
confidence: 72%
“…Though most mammalian GMB research is limited to humans and model organisms (e.g., rodents, non-human primates), recent studies demonstrate that host phylogeny [19], diet [20,21], life stage, and sex [22] affect GMB diversity and community membership. Moreover, field studies suggest that wildlife GMB community composition is sensitive to habitat disturbance [23][24][25], often resulting in reduced microbial diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that the gut microbiome can be used as an indicator of food resource use. For instance, black bear consuming processed anthropogenic foods host significantly degraded gut microbiomes [ 90 ], whereas brown bears with access to salmon host gut microbial communities that are distinguishable from populations limited to terrestrial food sources [ 85 ]. Given that marten consume a variety of prey across trophic levels, from terrestrial and aquatic environments and from both natural and anthropogenic sources, the gut microbiome of marten may be used to distinguish among animals consuming food items across a variety of sources and land covers with variable human influences.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings may reflect the marten’s comparatively simple gut morphology (i.e., lacking a cecum) and rapid gut passage rate from consumption to defecation. Rapid passage rates may preclude regulation by the immune system, and therefore may result in increased gut microbial variation among individuals–in addition to variation resulting from environmental and dietary perturbations [ 90 ]. Further, our sampling occurred during the winter when food resources are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…These are distributed in the states of Sonora, Chihuahua, Coahuila, Nuevo Leon, Tamaulipas, Durango, Zacatecas, San Luis Potosi, Sinaloa, Nayarit and Aguascalientes [1,[4][5][6] (see S1 Fig, available online). There have been reports of population reduction due to increased anthropogenic pressures on wildlife, habitat destruction (e.g., agriculture and livestock production), loss of natural prey/foods and rapid urbanization [4,[7][8][9]. Some health complications have been reflected in bears as a result of human-animal interaction such as physiological consequences of consuming low-energy foods could be a response to anthropogenic activity [10] or black bears alter movements in response to anthropogenic features with time of day and season [11].…”
Section: Introductionmentioning
confidence: 99%